(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Regarding the useful results concerned with an external radio-therapy in treatment of tumors, we consider in this paper a standard model of the human prostate phantom based on MIRD phantom for the Monte Carlo simulation in GEANT4 toolkit and also on MCNPX code for a prostate cancer treatment. We calculate the lateral as well as the dose profiles in the tumor region for both proton and alpha beams in a similar range, and finally having implemented the SOBP technique, we compare the results of the two beams in the corresponding codes used in this analysis.